Reminiscence‐Based Therapies for Depression: Should They Be Used Only With Older Adults?. (December 2013) - Hallford, David; Mellor, David
<x xml:space="preserve">Abstract</x> Reminiscence‐based therapies have been reliably evidenced to be an effective intervention for depression. However, to date, their use has been restricted primarily to older adults. This article reviews empirical findings related to the various functions of reminiscence and their correlates with mental health. Reminiscence‐based interventions and their effectiveness are then reviewed, with a particular focus on recent evaluations of structured reminiscence‐based therapies that utilize preexisting therapeutic frameworks for the treatment for depression. The exclusive use of reminiscence‐based therapies with older adult populations is then challenged, and it is argued that these approaches may be useful for reducing depression symptomatology for young and middle‐aged adults also. Considerations for the use of reminiscence‐based therapies in these populations are discussed, and future directions for research are presented.